A Glimpse of Blue Sheep (Pseudois nayaur) Hunting in Api Nampa Conservation Area (ANCA) Nepal - Yakha, Tek Bahadur; Chalise, Mukesh Kumar (Journal of Institute of Science and Technology, 2021)
Higher altitudes of Api Nampa Conservation Area have become a hunting destination for the local people bringing a threat to blue sheep and other wildlife. Blue sheep has been a national concern in Nepal due to being the main prey species of snow leopard and trophy hunting. The purpose of this paper is to examine the impact of hunters in Api Nampa Conservation Area (ANCA), Darchula, Nepal. This study was carried out around Api Nampa Conservation Area in 2016. Mixed methods of questionnaires were developed to collect data, and quantitative analysis was done by applying SPSS 16. A hundred percent of hunters like to hunt in this protected area. The hunted animals were goral, blue sheep, barking deer, boar and tahr. Site-specific characteristics like vegetation density, terrain and rugged land topography often vary markedly across surveys. Due to the regular and yearly use of grazing by the livestock in the area, it becomes imperative to study their feeding habits and document their food plants. Consequently, poaching and livestock grazing are important challenges for the conservation of blue sheep. Hunting, deforestation, forest fires, grazing and shifting agriculture are identified as major threats to the wildlife of Api Nampa Conservation Area. Envisioning, critical thinking, building partnership in decision-making, awareness, and stringent action against hunting activities must be adopted early. Api Nampa Conservation Area has received little research attention from grassland ecologists and specialists in pastoral management.